PENGELOLAAN KELAS BERBASIS MODERASI BERAGAMA PADA MATA PELAJARAN PENDIDIKAN AGAMA DAN BUDI PEKERTI DI KELAS IC SD MARDI YUANA SERANG - Siahaan, Anggel Veronika; Hidayat, Sholeh; Damanhuri, Damanhuri; Jamaludin, Ujang (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
This study aims to determine how classroom management based on religious moderation in Religious Education and Budi Pekerti subjects in class IC SD Mardi Yuana Serang. The research method used is qualitative with descriptive research type. The informants in this study were the principal, religion teacher, and IC class students. Data obtained through interviews, observation, documentation. The results of this study indicate that SD Mardi Yuana Serang conducted a needs analysis before the implementation of religious moderation-based classroom management. In its implementation, the teacher adjusts diversity in the classroom, namely prayers performed by each child according to their religion, followed by checking the attendance of students. Learning general religious subject matter supported by learning media, then discussions by distributing groups that are divided randomly so that children are involved in discussions with all friends without choosing. This process can be seen from the results of the written test as well as observations made.